Wide open [compact disc] - McDonald, Michael, 1952- (BMG, 2017)
This is Michael's first completely original release in nearly 17 years with 12 new songs produced by Michael and drummer Shannon Forrest (Toto). The album includes many guest artists and musicians including Forrest, guitarist-singer Warren Haynes (Allman Brothers Band, Gov't Mule), guitarist Robben Ford, bassist Marcus Miller, saxophonist Branford Marsalis, Amy Holland, David Paich and many more.